Decoding the antibody repertoire : high throughput sequencing of multiple transcripts from single b cells - DeKosky, Brandon (Springer, 2017)
This thesis outlines the development of the very first technology for high-throughput analysis of paired heavy and light-chain antibody sequences, opening the door for the discovery of new antibodies and the investigation of adaptive immune responses to vaccines and diseases. By designing two new technologies for sequencing multiple mRNA transcripts from up to 10 million isolated, single cells, the author directly addresses the limitations to provide information on the identity of immune receptor pairs encoded by individual B or T lymphocytes. Previous methods for high-throughput immune repertoire sequencing have been unable to provide such information. The techniques developed in this thesis have enabled comprehensive investigation of human B-cell repertoires and have been applied for the rapid discovery of new human antibodies, to gain new insights into the development of human antibody repertoires, and for analysis of human immune responses to vaccination and disease.
Includes index.
Keywords: B cells -- Research.; Immunoglobulins -- Analysis.; elektronické knihy; electronic books